Leadership experiences of elite football team physicians during the COVID-19 pandemic: a pilot study - Carmody, S.; Brar, G.; Massey, A.; Rosenbloom, C.; Gouttebarge, V.; Davison, M. (BMJ Leader, 2023)
Objectives: The purpose of this study was to explore the leadership experiences of elite football team physicians during the COVID-19 pandemic.